Hermeneutical Approach Used in The Translation of Swear Words Found in “Jakarta VS Everybody” Movie Into English - Dimas Adi Pratama; I Nyoman Muliana; I Gusti Ayu Agung Dian Susanthi (Journal of Comprehensive Science, 2026)
This study examines the translation of swear words in the Indonesian film Jakarta vs Everybody into English subtitles by applying a hermeneutical approach combined with audiovisual translation theory. The background of this research lies in the complexity of translating culturally bound and emotionally charged expressions, such as swear words, which require not only linguistic equivalence but also contextual and pragmatic interpretation. The objective of this study is to analyze how swear words are classified, translated, and contextually reconstructed across languages. This research employed a qualitative descriptive method with textual analysis, focusing on selected dialogue containing swear words and their corresponding subtitles. The findings reveal that swear words are categorized into several dominant themes, including scatological, sex organ, and sexual activities, each serving different communicative functions. In terms of translation strategies, cultural substitution, paraphrasing, euphemizing, and omission are frequently used to maintain naturalness, readability, and pragmatic equivalence under subtitle constraints. The discussion shows that translation involves a hermeneutical process of understanding, interpretation, and reformulation, often resulting in shifts in emotional intensity and cultural nuance. In conclusion, translating swear words in audiovisual media is a dynamic interpretive process in which translators act as cultural mediators to preserve meaning, function, and audience impact.